[Formula Presented] reaction near threshold in a chiral power counting approach - da Rocha, Carlos A. [UNESP]; Miller, Gerald A.; van Kolck, Ubirajara (American Physical Society (APS), 2000)
Power-counting arguments are used to organize the interactions contributing to the [Formula Presented] reactions near threshold. We estimate the contributions from the three formally leading mechanisms: the Weinberg-Tomozawa (WT) term, the impulse term, and the Δ-excitation mechanism. Subleading but potentially large mechanisms, including S-wave pion rescattering, the Galilean correction to the WT term, and short-ranged contributions are also examined. The WT term is shown to be numerically the largest, and the other contributions are found to approximately cancel. Similarly to the reaction [Formula Presented] the computed cross sections are considerably smaller than the data. We discuss possible origins of this discrepancy. © 2000 The American Physical Society.